Assessing suitability of different forms of coconut for usage in manufacturing of Paneer-like soft cheese - Paul, Preeti; Pinto, Suneeta V; Dharaiya, Chetan N; Chaudhary, Mamata L; R, Yashvantha; Vasava, Neha (Indian Journal of Dairy Science, 2020)
Coconut has been quietly gaining importance as a functional food around the world especially in southâ€“east Asia. Being a good source of medium chain triglycerides, minerals and to some extent protein, it has been considered as one of the â€œsuperfoodsâ€. The objective of the present study was to develop a paneer-like soft cheese using milk and coconut milk solids to improve the quality of fat in the final product. The aim was to maintain the fat in paneer by mixing low fat milk (3.0% fat) with coconut milk solids, which is high in coconut fat. Four types of coconut milk solid sources viz. coconut milk powder (spray-dried), coconut milk (freshly extracted), UHT treated coconut milk and desiccated coconut shreds were used to prepare acid coagulated soft cheese. Based on sensory acceptability, coconut milk powder (6%) and UHT treated coconut milk (10%) were selected and used to prepare soft cheese which was eventually analyzed for its sensory, textural and compositional attributes. Improvement in the fatty acid profile was observed by analyzing control and developed product by GC-MS. Sensory evaluation was carried out using 9-point hedonic scale. All the data was statistically analyzed and interpreted using ANOVA.